Ecological Studies of Certain Grasslands at Jhansienergy Structure and its Dynamics - Trivedi, B K; Mishra, G P (Annals of Arid Zone, 2016)
The present 'study was conducted in natural grassland at Air Field, Jhansi (780 35' E, 250 27' N and 275 m MSL). Sehima nervosum and Heteropogon contortus were the dominant perennial grasses. Through oxygen-bomb calorimeter caloric values of five compartments were estimated and energy budget and ecological efficiency were worked out. The results revealed that On dry weight basis roots exhibited the highest caloric value. The total net production of energy was 9759 k cal/m2/year whereas total loss of energy estimated was 3670 k cal/m2/year. Ecological efficiency of the community was 1.17 percent.